Indocyanine Green–Guided Pediatric Tumor Resection: Approach, Utility, and Challenges - Abdelhafeez, Abdelhafeez; Talbot, Lindsay; Murphy, Andrew J.; Davidoff, Andrew M. (Frontiers in Pediatrics, 2021)
Incomplete tumor resection increases the risk of local recurrence. However, the standard of care approach to distinguishing tumor tissue is less than optimal, as it depends on a conglomeration of preoperative imaging and visual and tactile indicators in real time. This approach is associated with a significant risk of inadequate resection; therefore, a novel approach that delineates the accurate intraoperative definition of pediatric tumors is urgently needed. To date, there is no reliable method for the intraoperative assessment of tumor extent and real-time differentiation between tumor- involved tissues and tumor-free tissues. Use of intraoperative frozen sections is challenging, time consuming, and covers a small surface area. Increased vascular permeability and impaired lymphatic drainage in the tumor microenvironment leads to an enhanced permeability and retention effect of small molecules. ICG is a fluorescent dye that when administered intravenously accumulates passively in the tumor because of EPR, thereby providing some tumor contrast for intraoperative real-time tumor recognition. Preclinical and clinical studies suggest that the tumor-to-background fluorescence ratio is optimized when imaging is obtained 24 h after dye injection, and many studies suggest using a high dose of ICG to optimize dye retention in the tumor tissue. However, in childhood cancers, little is known about the ideal dosing, applications, and challenges of ICG-guided tumor resection. This retrospective study examines the feasibility of ICG-guided tumor resection in common childhood solid tumors such as neuroblastoma, sarcomas, hepatic tumors, pulmonary metastases, and other rare tumors. Pediatric dosing and challenges related to the optimization of tumor-to-background ratio are also examined.